A Cold War state of mind: brainwashing and postwar American society - Dunne, Matthew W. (Culture, politics, and the Cold War, 2013)
"There is no 'behind the lines' any longer." -- The origins of brainwashing -- The many faces of the communist enemy -- Korean War POWs and a reevaluation of the national character -- Motherhood and male autonomy during the Cold War -- "A disquieting invasion of our mental domain." -- Hidden persuaders on the home front -- The limits of individuality in postwar America -- The legacy of brain warfare